Burns: dressings - Wasiak, Jason (BMJ Clin Evid, 2015)
INTRODUCTION: Burns are classified according to depth. This overview concerns the treatments for partial-thickness burns, which can be expected or have the potential to heal spontaneously (superficial partial-thickness and mid-dermal partial-thickness burns). Injuries that involve the deeper part of the dermis and require surgical treatments to achieve healing are not the focus of this overview. METHODS AND OUTCOMES: We conducted a systematic overview and aimed to answer the following clinical question: What are the effects of treatments for partial-thickness burns? We searched: Medline, Embase, The Cochrane Library, and other important databases up to January 2014 (BMJ Clinical Evidence overviews are updated periodically; please check our website for the most up-to-date version of this review). RESULTS: At this update, searching of electronic databases retrieved 322 studies. After deduplication and removal of conference abstracts, 193 records were screened for inclusion in the overview. Appraisal of titles and abstracts led to the exclusion of 160 studies and the further review of 33 full publications. Of the 33 full articles evaluated, two systematic reviews and two RCTs were added at this update. We performed a GRADE evaluation for 30 PICO combinations. CONCLUSIONS: In this systematic overview, we categorised the efficacy for 10 interventions, based on information relating to the effectiveness and safety of alginate dressing, biosynthetic dressing, chlorhexidine-impregnated paraffin gauze dressing, hydrocolloid dressing, hydrogel dressing, paraffin gauze dressing, polyurethane film, silicone-coated nylon dressing, silver-impregnated dressing, and silver sulfadiazine cream.